The Girls Who Made a Difference - Howat, Irene; Nang Chan Yeema (Denmark Christian Focus, 2007)
Would you like to make a difference? These ten girls grew up to do just that. Susanna's children changed their country; Monica's son changed the church; Ann's romance taught Burma about the love of Christ $1! =s
Keywords: Adult Nonfiction